Exploring the Identity of Acehnese Female Celebgrams: Hedonistic Lifestyle and Sharia Challenges in the Digital Age - Tina, Agustinar; Mufida, Laila (IAIN Langsa, 2025)
Abstract This research explores the challenges faced by female influencers from Aceh in managing their digital identities on social media, considering the cultural shift towards a modern lifestyle that often conflicts with Islamic values. Although social media provides a space for expression, social and religious pressures invite identity conflicts. This study employs a virtual ethnographic approach to understand how Acehnese women blend religious principles with the demands of modern lifestyles. Using a descriptive qualitative and virtual ethnographic approach, the research examines the experiences of Acehnese female influencers in navigating their digital identities on social media. Through observations and in-depth interviews, this study investigates the interactions between cultural norms and hedonistic lifestyles in the conservative context of Aceh, leading to insights about self-representation. The findings indicate that Acehnese female influencers face significant challenges in reconciling traditional identities with modernity on social media. Despite exposure to hedonistic lifestyles, they strive to remain faithful to their religious and cultural values by creating positive and educational content. Community support is essential in creating an inclusive space that enables them to act as agents of change while maintaining a balance between modernity and tradition. The implications of this research highlight the need for community support to assist Acehnese female influencers in integrating traditional values into their digital content, thereby creating a balance between modernity and Islamic law. Keywords: Digital Identity, Hedonistic Lifestyle, Cultural Conflict